Hubungan Pengetahuan Kosmetik Rambut Modern Terhadap Perilaku Pemilihan Kosmetika Perawatan Rambut - Nabila Aulia Rahmah; Elvyra Yulia; Neneng Siti Silfi Ambarwati (Inkubis : Jurnal Ekonomi dan Bisnis, 2022)
Knowledge about hair cosmetics is important for someone to know, especially for students as consumers in order to choose hair care cosmetics appropriately according to the needs and types of hair and scalp. This study aims to determine the Relationship of Modern Hair Cosmetics Knowledge to Hair Care Cosmetics Selection Behavior (Study on Cosmetology Students of Jakarta State University Class of 2019). The research method used is the survey method. The sample in this study is the entire number of cosmetology students of the Class of 2019 which amounts to To a significant extent shows results smaller than on a value that means that the relationship between the two variables is linear. Then in the results of the hypothesis test conducted using a t-test whose results there was a positive relationship between knowledge of modern hair cosmetics and the selection behavior of hair care cosmetics (study on cosmetology education students of Jakarata State University class of 2019).